1.050 Engineering Mechanics I: Beam Elasticity - Problem Solving Technique and Examples
1.050 Engineering Mechanics I: Beam Elasticity - Problem Solving Technique and Examples
1.050 Engineering Mechanics I: Beam Elasticity - Problem Solving Technique and Examples
Lecture 25:
and examples
Handout
1
I. Dimensional analysis
1. On monsters, mice and mushrooms Lectures 1-3
2. Similarity relations: Important engineering tools Sept.
IV. Elasticity
7. Elasticity model – link stresses and deformation Lectures 20-31
8. Variational methods in elasticity
Oct./Nov.
V. How things fail – and how to avoid it
9. Elastic instabilities
10. Plasticity (permanent deformation) Lectures 32-37
Dec. 2
11. Fracture mechanics
1
1.050 – Content overview
I. Dimensional analysis
IV. Elasticity
Lecture 20: Introduction to elasticity (thermodynamics)
d 4ξ z fz
=
dx 4 EI
Integration provides solution for displacement
Solve integration constants by applying BCs
Note:
E = material parameter (Young’s modulus)
I = geometry parameter (property of cross-section)
fz = distributed shear force (force per unit length)
2
4-step procedure to solve beam elasticity
problems
d 4ξ z fz d 4ξ z
= EI = f z Shear force density
dx 4 EI dx 4
d ξz
3
Q d 3ξ z
3
=− z − EI = Qz Shear force
dx EI dx 3
d 2ξ z M d 2ξ z
2
=− y − EI = M y
Bending moment
dx EI dx 2
dξ z dξ
= −ω y − z =ω y Rotation (angle)
dx dx
ξ z ξz Displacement
3
Step-by-step example
z p = force/length
l length
EI
Step 1: BCs
ξ z (0) = 0
x=0
ω y (0) = 0
ξ z (l) = 0
x=l
M y (0) = 0
7
d 4ξ z f d 4ξ z p
4
= z = −
dx EI dx 4 EI
p applied in
negative z-
direction
p
Step 3: Integration ξ z''' = − x + C1
EI
p x 2
ξ z'' = − + C1 x + C2
p EI 2
ξ z'''' = − p x3 x 2
EI ξ z' = − + C1 + C2 x + C3
EI 6 2
4
p x x3 x 2
ξz = − + C1 + C2 + C3 x + C
8
4
EI 24 6 2
4
Step 4: Apply BCs
p Qz
ξ z''' = − x + C1 = −
EI EI
p x2 M
ξ z'' = − + C1 x + C2
= − y
EI 2
EI
3 2
p x x
ξ z' = − + C1 + C2 x + C3 = −ω y
EI 6 2
4
p x x3 x2
ξz = − + C1 + C2 + C3 x + C4
EI 24 6 2
ξ z (0) = 0 → C4 = 0
ω y (0) = 0 → C3 = 0
p l4 l3 l2
ξ z (l) = 0 → − + C1 + C2 = 0
EI 24 6 2
p l2
M y (0) = 0 → − + C1l +C 2= 0
EI 2
⎛ l4 ⎞ p 5
⎛l 3
l ⎞⎛ C ⎞ p ⎜ ⎟
2
C1 = l
⎜ ⎟ 1
2 ⎟⎜⎜ C ⎟⎟ = EI ⎜ l 2 ⎟
24 EI 8
⎜⎜ 6 ⎜ ⎟
⎝l 1 ⎟⎠⎝ 2 ⎠ ⎜ ⎟ C2 = −
p 1 2
⎝ 2 ⎠ EI 8 10
5
Solution:
⎛ 5 ⎞
Qz (x) = p⎜ x − l ⎟
⎝ 8 ⎠
⎛ 1 2 x2 5 ⎞
M y (x) = p⎜⎜ l + − lx ⎟⎟
⎝8 2 8 ⎠
p ⎛1 2 x3 5 ⎞
ω y (x) = ⎜⎜ l x + − lx 2 ⎟⎟
EI ⎝8 6 16 ⎠
p ⎛ 1 2 2 x4 5 3 ⎞
ξ z (x) = − ⎜⎜ l x + − lx ⎟⎟
EI ⎝ 16 24 48 ⎠
11